Gestão democrática e seus reflexos no ensino da matemática - LIMA, Joana Darc Pereira de (2022)
The work is the result of a study on democratic management and the teaching of Mathematics at a Municipal Elementary School in São Domingos do Capim / PA. The research reflects on the relationship between management, teachers and students within the school. In this perspective, it addresses issues involving teaching, pedagogical work, didactics, curriculum and school action plans. For that, questions are elucidated at deeper levels about the performance of school management, the work of the teacher and the feeling of the student in relation to the space where he studies and the subject of Mathematics in the 5th year of Elementary School. A descriptive and bibliographic research was carried out, with a qualitative approach, in which an interview with open and closed questions was used as an instrument of data collection. During the study, some relevant aspects about the management function in promoting the improvement of the teaching-learning quality were highlighted and it was found that the role of school managers must go beyond the administration of material resources and respond to administrative aspects, it must be articulated with pedagogical management in the classroom and the way students understand school curriculum and its relationship with mathematics.